7-Ketocholesterol disturbs RPE cells phagocytosis of the outer segment of photoreceptor and induces inflammation through ERK signaling pathway. (December 2019) - Yang, Chen; Xie, Lirong; Gu, Qing; Qiu, Qinghua; Wu, Xingwei; Yin, Lili
Abstract: 7-Ketocholesterol (7KCh), an oxidized form of cholesterol, is present at a high level in drusen and has been believed to play a role in the pathogenesis of age-related macular degeneration (AMD). Therefore, we developed a rat model to study the direct impact of 7KCh on retina. We delivered 7KCh to the rat retina by intravitreal injection using hydroxypropyl-β-cyclodextrin as a vehicle. We observed that 7KCh mainly deposited in the retinal pigment epithelial (RPE) cells and induced marked photoreceptor apoptosis. Transmission electron microscope examination demonstrated cytoplasmic vacuoles in RPE cells and the microvilli detached from the outer segment after 7KCh treatment. In vitro experiments also revealed that RPE cells could take up 7KCh in culture. Moreover, 7KCh up-regulated IL-1βmRNA, TNF-αmRNA, IL-6 mRNA, and IL-1β secretion of RPE. U0126, a MEK1/2 inhibitor, down regulated the expression of these inflammation factors. Our findings may help elucidate the potential role of 7KCh in the pathogenesis of AMD. Highlights: RPE cells can specifically take up 7KCh in fundus oculi. 7KCh induces photoreceptor apoptosis by hampering RPE from digesting POS. 7KCh induces ARPE-19 cell inflammation through the ERK signaling pathway.